ANALYSIS OF DEFORMATION OF TYPICAL FORMS SURROUNDING ROCK MASSIF FOR MINE WORKINGS SUPPORT RECOVERY - Sergey S. Tsibaev; Alexey A. Renev; Qing-duo Wan; Feng-hai Yu (Известия Томского политехнического университета: Инжиниринг георесурсов, 2021)
Relevance. More than 75 % of underground mine workings are supported by anchorage nowadays. In the case of long-term mine workings maintenance the deformations of surrounding rock massif and anchoring elements occur. The surrounding rock massif typical forms deformations determination in order to develop the design solutions and substantiate anchorage parameters is currently urgent scientific and practical task. Especially it is important in case of mine workings support repair or recovery stages. The main aim is mine working anchorage design solutions and parameters substantiate during the repair and recovery stages. Methods: field measurements, statistical processing of results. Results. The paper introduces the description, causes of occurrence and manifestation forms of geomechanical processes in surrounding rock massif supported by anchorage. Based on the long-term field measurements six forms of rock massif typical deformations have been established.The roof bridging begins with decompaction of rocks, which causes rocks stratification under the influence of gravity. This results in cavities formation and lower layers separation from upper ones. Because of formation of the plastic deformation zone around mine workings the extraction and dumping coal from walls occur. Coal and rocks are in an unbound state and are kept in balance due to the forces of friction and resistance of the support in the zones of plastic deformations. Its width depends on many factors such as the working width and the internal friction angle. The coefficient of stress concentration in the walls rises up due to growth of mine working widht.